Human Ro ribonucleoprotein particles: characterization of native structure and stable association with the La polypeptide. - Boire, G (1990)
Anti-Ro autoantibodies, found in sera of patients with systemic lupus erythematosus, Sjogren's syndrome, and related diseases, target the Ro ribonucleoprotein particles (RNPs). Although the polypeptide and RNA components of the Ro RNPs have been characterized, much less is known about the native structure of these particles. We have now characterized by biochemical techniques intact Ro ribonucleoprotein particles from cultured HeLa cells. These particles segregated in three discrete subpopulations with characteristic physicochemical properties: one containing hY5 RNA (RohY5 particles), one containing only hY4 RNA (RohY4 particles) and one with hY1, hY3, and hY4 RNAs (RohY1-hY4 particles). The RohY5 particles were purified free of contaminating ribonucleoproteins; both the La and the 60-kD Ro polypeptides were stable components of this portion of the Ro RNPs. The La RNPs co-purified with the RohY4 particles and contaminated the RohY1-hY4 RNPs. The stable association between the La and the 60-kD Ro polypeptides provides a potential macromolecular target for the linked set of anti-Ro and anti-La antibodies, and suggests a possible functional association of these polypeptides.